Draft Tenth Five Year Plan 2002-2007 and Annual Plan 2002-2003 Volume-III Government of Uttaranchal - Planning Commission (Planning Commission, 2002)
Draft Tenth Plan 2002-07 and Draft Annual plan 2002-03 - Proposed Outlays, 10th Plan (2002 - 07) and Annual Plan 2002-03 - Scheme Wise Outlay, Physical Targets and Achievements, Draft Tenth Plan(2002-2007) Proposals For Spillover and On Going Programme/ Projects As In Annexure - I, Draft Tenth Plan (2002-2007) - Proposals For Programmes/ Projects - New Schemes, Special Component Plan For Scheduled Castes (SCP) Draft 10th Plan -2002-07 and Annual Plan 2002-03, Draft Tenth Plan 2002-2007 and Draft Annual Plan 2002-03 Financial Outlay : Proposals For TSP, Draft Tenth Plan 2002-2007 and Draft Annual Plan 2002-03 Pradhan Mantri Grammodyog Yojana - Outlay / Expenditure
Draft Tenth Five Year Plan 2002-2007 and Annual Plan 2002-2003 Volume-III
Government of Uttaranchal